The Effectiveness of Wisdom Training on Academic Emotions, Academic Motivation and Subjective Vitality in Students - Masoomeh Azizi; Abolghasem Yaghoobi (پژوهشنامه روانشناسی مثبت)
The present study examined the effectiveness of wisdom training on academic emotions, academic motivation and subjective vitality in students. The study method was semi-experimental and its design was pretest, post-test with control group and follow-up stage. The statistical population involved all female students of the first secondary school in the academic year of 2023-2024 in Hamadan, Iran. In doing so, 42 students were selected by available sampling method and randomly divided in experimental (21 individual) and control group (21 individual). After grouping and conducting the pre-test, wisdom training sessions were provided to the experimental group. Then a post-test was taken from both groups. The data collection tools were three questionnaires of academic emotions, academic motivation and subjective vitality. In order to analyze the data, mixed method analysis of variance was used. The findings indicated that wisdom training had a significant effect on academic emotions, academic motivation and subjective vitality of students, and this effect was still stable in the follow-up phase after four months. Therefore, it can be concluded that wisdom training fosters academic emotions, strengthens academic motivation in students, and these factors together increase their subjective vitality. Based on this, it is suggested that teachers design and develop wisdom interventions in schools for positive learning, motivational and happiness-enhancing results for students. Introduction* Research shows application of positive psychology in the students’ curriculum can lead to improved mental health and acquisition of positive emotional experiences. Previous studies show that negative emotions lead to distraction and reduced efficiency in the learning process, but positive emotions contribute to better learning and students’ psychological well-being (Lou & Xu, 2022). Subjective vitality is one of the variables that significantly affects students’ personal and academic success; Low subjective vitality causes irritability and fatigue, whereas high subjective vitality results in improved performance (Haghbin & Sheikholeslami, 2019). Another important construct is academic motivation, the decline of which leads to poor academic performance leaving a negative impact on mental health (Anttila et al., 2023). Mindfulness education is also one of the most important topics in positive psychology (Montiel et al., 2021).  By deepening and broadening students' perspectives, it encourages reflection and thinking about their own and others' life experiences, which can help achieve purposefulness, motivation, positive emotions, and a sense of vitality in students. Accordingly, the present study examined whether mindfulness education could significantly affect academic emotions and motivation, and increase subjective vitality in students. Method This was a quasi-experimental study with a pretest-posttest control group design. The participants were selected by convenience sampling from among female students in the first year of middle school in the academic year 2023-2024 in Hamadan, Iran. The research instruments included the Achievement Emotions Questionnaire, Subjective Vitality Scale, and Academic Motivation Scale. Ethical considerations, such as voluntary participation and the right to withdraw from the study, were observed, along with confidentiality of the information. To develop the mindfulness education program, thematic analysis was used with a sequential exploratory design. For assessing the content validity of the package, the Content Validity Index was utilized, which yielded a value of 0.88 and above for the components of this package, indicating appropriate content validity. In the pretest, the questionnaires were administered to both groups. Then, the experimental group received the intervention over two months (8 one-hour sessions a week). Subsequently, both groups responded to the questionnaires on the posttest and after a four-month follow-up period. Descriptive statistics and mixed ANOVA on SPSS software were employed for data analysis. Results Before data analysis, the assumptions for the mixed ANOVA were examined. The normal distribution of the data was assessed and confirmed using the Kolmogorov-Smirnov test (p > 0.05). Levene's test was also conducted to determine the homogeneity of variances, revealing no significant differences in the variances of positive academic emotions, academic motivation, and subjective vitality (p >0.05), thus confirming the assumption of homogeneity of variances. The assumption of homogeneity of the covariance matrix was assessed using M. Box's criterion (p <0.05, F= 1.60, Box's M=17.97) showing that this assumption was not violated (p>0.05). Mauchly's test was used to examine the equality of the variance-covariance matrix of the variables, with results showing (Mauchly= 0.89, p = 0.169> 0.05) for academic motivation, (Mauchly= 0.78, p = 0.129> 0.05) for negative academic emotions, (Mauchly= 0.95, p= 0.234> 0.05) for positive academic emotions, and (Mauchly = 0.58, p = 0.073> 0.05) for subjective vitality, confirming that the assumption of equality of the variance-covariance matrix (p > 0.05) was established. The results of mixed ANOVA revealed a significant main effect for time in all variables meaning that the mean scores related to motivation, academic emotions, and subjective vitality were significantly different from pretest to posttest and follow-up (p < 0.05). The main effect of group membership (groups) was also significant for the research variables, suggesting a significant difference between the groups in motivation scores, academic emotions, and subjective vitality (p < 0.01). The Group x Time interaction also showed significant differences in all variables between the two groups (p < 0.01) suggesting a significant difference in academic motivation, positive and negative academic emotions, and subjective vitality from pretest to posttest and follow-up. The partial eta squared value indicated that 21% of the variance in academic motivation, 22% in negative academic emotions, 17% in positive academic emotions, and 31% in subjective vitality could be explained by group membership. The results of Bonferroni's post hoc test showed that there were significant differences in the mean scores of academic motivation, positive and negative academic emotions, and subjective vitality between the pretest and posttest and follow-up phases, indicating that mindfulness education significantly affected the dependent variables (p < 0.05). However, the difference in the mean scores of the variables was not significant between the posttest and follow-up stages, showing the stability of the results (p > 0.05). Conclusion The present study examined the effect of mindfulness education on academic emotions, academic motivation, and subjective vitality in female middle school students in Hamedan, Iran. The findings, in line with the results of Ardlet (2018), indicated that mindfulness education had a significant effect on academic emotions. In explanation for this finding, it can be stated that mindfulness is conceptualized as a set of skills that includes making the best situational decisions based on knowledge, experience, and moral virtues. Mindfulness education is vital for helping students navigate the challenges of their educational journey and develop the ability to control their emotional states. Therefore, it can facilitate positive adaptation to life's adversities in students. The findings further showed a positive and significant effect for mindfulness education on students' academic motivation, which is consistent with the results of Yulianto and Indriayu (2023). According to Deci and Ryan (2008), supporting students' autonomy enhances intrinsic motivation, which is a crucial aspect of the desire to learn. Thus, mindfulness education can foster the experience of autonomy and establish or maintain academic motivation in students.  Finally, mindfulness education had a positive and significant effect on increasing students' subjective vitality, which is in line with the findings of Shoghi et al. (2022). Mindfulness education encourages the constructive use of emotions. Students learn to feel confident in identifying and understanding their feelings. Mindful problem-solving enhances coping strategies for effective stress management and impulse control in students, enabling them to pursue their academic and personal goals with vitality. The present study was constrained by certain limitations. First, data was collected from a sample of female students in grades seven, eight, and nine, where the differences in developmental levels can be considered a limitation. Therefore, caution should be practiced in generalizing the results to other life stages and educational levels. Another limitation was the use of self-report measures; hence, it is better to use objective measures such as interviews in the future studies. Ethical considerations: All ethical considerations were observed, including ensuring the confidentiality of participants’ identities and obtaining informed consent from all participants. Authors’ contributions: All authors contributed to the study. The first author conducted the intervention and data collection and wrote the introduction and method sections. The second author wrote the results and discussion sections and edited the initial draft. Conflict of interest: The authors declared no conflicts of interest. Funding: The authors did not receive any financial support for this study. Acknowledgments: The authors thank all participants for their time and contribution to this study. *. Corresponding author